The Principal’s Leadership and Academic Supervision for Teacher’s Performance - Rosalina, Rosalina; Lian, Bukman; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2023)
This study was conducted with the aim of analyzing and describing: 1) the influence of madrasa principal leadership on teacher performance; 2) the effect of academic supervision of madrasa supervisors on teacher performance; 3) the influence of the leadership of the madrasah principal and academic supervision of the supervisor together on teacher performance. The method used in this study refers to quantitative descriptive. This research was conducted at Madrasah Aliyah in Lempuing Jaya District with a sample of 64 people. Data collection techniques were carried out through questionnaires, observation and documentation. The validity test was carried out through expert and construct validation tests, and the instrument was declared valid. Data analysis was carried out through prerequisite tests, namely normality, linearity, multicollinearity and heteroscedasticity. After testing the prerequisites, the analysis was carried out through a regression test. The results obtained state that partially 1) the leadership of the madrasa principal has an effect on teacher performance, with a fairly high influence, namely 47.4%. 2) Academic supervision of supervisors also contributes to the influence of teacher performance which is categorized as high enough, namely 55.8%. Simultaneous testing stated that the leadership of the madrasah principal and academic supervision by the madrasa supervisor contributed quite a high influence to the teacher’s performance, namely 62.3% while the remaining 37.7%. Therefore, the hypothesis regarding the effect of the two independent variables on the dependent variable is accepted.